Consistent Belief in a Good True Self in Misanthropes and Three Interdependent Cultures. (6th June 2017) - De Freitas, Julian; Sarkissian, Hagop; Newman, George E.; Grossmann, Igor; De Brigard, Felipe; Luco, Andres; Knobe, Joshua
Abstract: People sometimes explain behavior by appealing to an essentialist concept of the self, often referred to as the true self. Existing studies suggest that people tend to believe that the true self is morally virtuous; that is deep inside, every person is motivated to behave in morally good ways. Is this belief particular to individuals with optimistic beliefs or people from Western cultures, or does it reflect a widely held cognitive bias in how people understand the self? To address this question, we tested the good true self theory against two potential boundary conditions that are known to elicit different beliefs about the self as a whole. Study 1 tested whether individual differences in misanthropy—the tendency to view humans negatively—predict beliefs about the good true self in an American sample. The results indicate a consistent belief in a good true self, even among individuals who have an explicitly pessimistic view of others. Study 2 compared true self‐attributions across cultural groups, by comparing samples from an independent country (USA) and a diverse set of interdependent countries (Russia, Singapore, and Colombia). Results indicated that the direction and magnitude of the effect are comparable across all groups we tested. The belief in a good true self appears robust across groups varying in cultural orientation or misanthropy, suggesting a consistent psychological tendency to view the true self as morally good.